Synthesis of isoquinoline derivatives as potential drug molecules active against prostate cancer - Karakaya, Halenur. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Cancer is the most common neoplasm of the prostate in developed countries. About 80% of prostatic tumors are based on elevated levels of androgens because androgen stimulates the cellular proliferation of human prostate cancer. Therefore, deprivation of androgen level constitutes a good strategy in order to treat castrationresistant prostate cancer. Enzymes in androgen biosynthesis are favorable targets, such as CYP17A1. Although the androgens are secreted from three different sites, namely the testes, adrenal glands, and PCa cells, androgen production depends on catalysis by one enzyme, CYP17, which is also known as P450-C17. Being a pivotal enzyme in the biosynthetic route to steroidal hormones, CYP17A1 has a key role in the conversion of progesterone and pregnenolone to androstenedione and dehydroepiandrostenedione (DHEA) respectively, which constitute as the direct precursors of 5α- dihydrotestosterone (DHT) and testosterone (T). Since the crystal structure of CYP17 has been absent for a long term, natural substrates (pregnenolone and progesterone) have been used as scaffolds of potential drug candidates. Although Abiraterone was launched as a potent steroidal CYP17 inhibitor, due to the potential side effects of steroidal CYP17A1 inhibitors resulting from inhibition of other steroid receptors, there is a certain need to develop nonsteroidal inhibitors. In this project, several derivatives of a nonsteroidal lead compound were designed: Mainly the synthesis of isoquinoline derivatives was endeavored. Besides, a library of final products was built by synthesizing several aromatic carboxamides including benzofuran-2-carboxylic acid, benzo[b]thiophene-2-carboxylic acid and 4-(1H-tetrazol-5-yl)benzoic acid derivatives.
Keywords: Prostate -- Cancer.; Isoquinoline.